Transfemoral Osseointegration for Amputees with Well-Managed Diabetes Mellitus - Jason S. Hoellwarth, MD; Shakib Al-Jawazneh, MD; Atiya Oomatia, BEng(Biomed); Kevin Tetsworth, MD, FRACS; Munjed Al Muderis, MBChB (JBJS Open Access)
Background:. The most common reason for lower-extremity amputations remains the management of complications of diabetes mellitus (DM) and/or peripheral vascular disease. Traditional socket prostheses remain the rehabilitation standard, although transcutaneous osseointegration for amputees (TOFA) is proving a viable alternative. Limited studies of TOFA for vascular amputees have been published, but no study has focused on TOFA for patients with DM, neglecting this important patient population. The primary aim of the present study exploring this potential care option was to report the frequencies and types of adverse events following TOFA for patients with well-controlled DM. The secondary aims were to report their mobility and quality-of-life changes. Methods:. A retrospective review was performed of 17 consecutive patients with well-controlled DM who had undergone unilateral transfemoral TOFA from 2013 to 2019 and had been followed for at least 2 years. Outcomes were perioperative complications, additional surgery (soft-tissue refashioning, debridement, implant removal, periprosthetic fracture treatment), mobility (daily prosthesis wear hours, K-level, Timed Up and Go Test, 6-Minute Walk Test), and patient-reported outcomes (Questionnaire for Persons with a Transfemoral Amputation, Short Form-36). Results:. There were no perioperative systemic complications, deaths, or proximal amputations. Two patients (12%) sustained a periprosthetic fracture following a fall, managed by internal fixation with implant retention, and regained independent ambulation. Eight patients (47%) had additional surgery or surgeries for non-traumatic complications: 4 (24%) had soft-tissue refashioning, 3 (18%) had debridement, and 3 others had implant removal with subsequent revision osseointegration for aseptic loosening (1) or infection (2). The proportion of patients wearing their prosthesis at least 8 hours daily improved from 5 (36%) to 11 (79%) of 14 (p = 0.054). The proportion of patients who achieved at least K-level 2 improved from 6% to 94% (p < 0.001). Other changes were not significant. Conclusions:. Contraindicating TOFA for all patients with DM seems draconian. Patients with well-controlled DM experienced significant mobility improvements, although additional surgery was somewhat common. Improvements in selection criteria or surgical technique to reduce risks are needed so that TOFA can be routinely considered for amputees with well-controlled DM. Level of Evidence:. Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.